The Relationship between Strategic Performance Measurement System and Organisational Capabilities: The Role of Beliefs and Boundary Control Systems - Mohamed, Rapiah; Wee, Shu Hui; Abdul Rahman, Ibrahim Kamal; Abdul Aziz, Rozainun (Asian Journal of Business and Accounting, 2014)
This paper examines the relationship between strategic performance measurement systems (SPMS) and organisational capabilities, i.e. market orientation, organisational learning, innovation and entrepreneurship. It uses the levers of control framework suggested by Simons (1999) and examines beliefs and boundary control systems as a potential moderator in the link between SPMS and organisational capabilities. The data was collected via a mail survey of top management of Malaysian listed companies. We find that the beliefs and boundary control system partly moderates the relationship between SPMS design and use and overall organisational capabilities. Further, we also find that beliefs and boundary control system moderates the relationship between SPMS design and use, and innovation and entrepreneurship. Implications of these findings are discussed in this paper. Keywords: SPMS; Levers of Control Framework; Organisational Capabilities; Private Sector JEL classification: M41